Effective treatment of advanced lung adenocarcinoma with paraneoplastic leukemoid reaction with Lorlatinib: a case report - Niu, Ruiqi; Zhang, Yiruo; Pang, Jingdan; Zhou, Qing; Lei, Yu; Du, Yingying (Frontiers in Oncology, 2024)
Background Lorlatinib is a new generation ALK kinase inhibitor. We describe a 52-year-old patient with ALK-positive advanced lung adenocarcinoma who achieved remission after multi-line therapy combined with paraneoplastic leukemoid reaction treated with Lorlatinib. Case report A 52-year-old male patient was diagnosed with stage IV right lung adenocarcinoma, ALK: (+), previously received oral Crizotinib and Alectinib. Blood routine showed white blood cells abnormally elevated after disease progression, and maximum white blood cell count was 179.14×10^9/L. The patient was enrolled in study entitled “a phase II, multicenter, open-label, dual-cohort study to evaluate the efficacy and safety of LORLATINIB monotherapy in ALK inhibitor-treated locally advanced or metastatic ALK-positive non-small cell lung cancer patients in China”. With oral Lorlatinib, the white blood cell count decreased from 179.14×10^9/L to normal after two weeks of administration. PFS was 4.5 months. When follow up imaging showed lesions progression, the white blood cell count increased again, diagnosing a paraneoplastic leukemic reaction. OS was 5.2 months. Conclusion In this case, fourth-line Lorlatinib treatment is effiective in ALK-positive advanced patient with paraneoplastic leukemoid reaction. ClinicalTrials.gov Identifier: NCT03909971